Interpersonal communication : everyday encounters - Wood, Julia T. (Australia : Wadsworth Publishing Company, 2013)
Interpersonal communication : everyday encounter, 7e will help you build the skills you need to become a better communicator.
Part I: The fabric of interpersonal communication -- 1. A First look at interpersonal communication -- 2. Communication and personal identity -- 3. Perception and communication -- 4. The World of words -- 5. The World beyond words -- 6. Mindful listening -- Part II: Weaving communication into relationships -- 7. Emotions and communication -- 8. Communication climate: The Foundation of personal relationships -- 9. Managing conflict in relationships -- 10. Friendships in our lives -- 11. Committed romantic relationships -- 12. Communication in families --
Includes bibliographical references and index.
Keywords: COMMUNICATION